PENGARUH BEBAN KERJA TERHADAP STRES KERJA KARYAWAN PADA UPDK PLTD GUNUNG MALANG BALIKPAPAN - Annisa, Rizka Nurul; Anwar, Anwar; Kurniawan, Agung Widhi; Haeruddin, M. Ikhwan Maulana; Dipoatmodjo, Tenri S. P. (MOTIVASI, 2024)
Purpose– This research aims to determine the effect of workload on employee work stress at UPDK PLTD Gunung Malang Balikpapan.Design/methodology– The type of research used is associative quantitative research. The sampling technique was carried out using saturation sampling. The sample used in this research was 48 respondents. The data used in this research is primary data. Methods of data collection using the method of questionnaire, using a skala likert. Data analysis used in this research is quantitative analysis. The data analysis technique used are simple linear regression analysis, t test, and coefficient of determination with the help of the SPSS version 23 application.Findings - The results of the research based on simple linear regression show that workload has a positive effect on employee work stress at UPDK PLTD Gunung Malang Balikpapan with the equation Y= -12,370 + 1,260X. The results of the t test hypothesis show that there is a significant effect of workload on employee work stress at UPDK PLTD Gunung Malang Balikpapan. The coefficient of determination value shows that the workload variable affects the high and low level of employee work stress by 31,5%, while the rest is influenced by other variables outside this study.